Differently unequal: Zooming-in on the distributional dimensions of the crisis in euro area countries - Marco D'Errico; Corrado Macchiarelli; Roberta Serafini (London School of Economics and Political Science (LSE), European Institute, 2015)
This paper discusses how income inequality developed during the current crisis in euro area countries, as well as the role played by each income source. Based on an extended definition of income – including additional components which do not appear in the standard Eurostat definitions – we complement the information provided by the Gini index and quantile ratios by computing an alternative inequality indicator, developed by Zenga (2007), and its decomposition by income source. While broadly confirming the distributional effect of the crisis documented in previous studies, we find that in specific countries the level of inequality appears higher when alternative measures are taken into account, and that the rise of inequality since 2008 has not been as modest as previous studies would suggest. The paper further looks at how the distribution of income has evolved during the crisis by income quantile groups (i.e. 'zooming-in'). The results point to varying contribution of labour income in 2011 compared to 2007. In addition, while the impact of individual households' characteristics shows a non-linear pattern across income quantile groups before the crisis, such dispersion has decreased in 2011. We argue that, on the basis of our analysis, not only euro area countries are "differently unequal" in that inequality has developed in a very peculiar way in different countries, but also that it needs to be tackled at a finer level of analysis.
Keywords: 330; inequality curve; income distribution; source decomposition; extended income definition; crisis